PENGARUH NET PROFIT MARGIN, UKURAN PERUSAHAAN, STRUKTUR ASET DAN PROFITABILITAS TERHADAP KEBIJAKAN UTANG - Permata Sari, Yunani Putri (Universitas Slamet Riyadi, 2015)
Debt policy is determining how much debt the company will be used to fund assets indicated by the ratio of total debt to total assets. Factors that influence the debt policy in this study is limited to the net profit margin, the size of the company, asset structure and profitability. The purpose of this study was to analyze the significance of the effect of net profit margin, the size of the company, the structure of assets and profitability partially or simultaneously to the debt policy on manufacturing companies in Indonesia Stock Exchange. In conclusion, no significant effect independent variable is the net profit margin, the size of the company, the structure of assets and profitability partially or simultaneously to the dependent variable is the policy of debt at a manufacturing company in Indonesia Stock Exchange. Keywords: net profit margin, size of the company, asset structure, profitability, debt policy